TENDENCIES OF USING ECONOMIC ANGLICISMS IN THE UZBEK LANGUAGE (The Conference Hub, 2025)
This article explores the increasing tendency of using economic Anglicisms in the Uzbek language. It analyzes the reasons behind their adoption, the socio-linguistic factors influencing their spread, and the domains where these borrowings are most prevalent. The study also discusses the adaptation processes of these terms into Uzbek phonology and morphology, highlighting their impact on the national lexicon and linguistic identity. Special attention is paid to the functional and semantic roles of Anglicisms in the fields of business, finance, and media.